Penatalaksanaan Holistik Infeksi Dengue pada Pria Pra Lansia dengan Pengetahuan Preventif Kurang Melalui Pendekatan Kedokteran Keluarga - Annisa Yulida Syani; Sahab Sibuea (MAJORITY, 2020)
Dengue Fever (DF) and Dengue Hemorrhagic Fever (DHF) are diseases transmitted through Aedes sp. This infection in tropical and subtropical climates. Prevention with hygiene and healthy living habits and maintaining a clean environment. Family doctors is important to treating sufferres, doctors must pay attention to the environment and daily behavior of sufferers and their families that have an impact on the recurrence process or spread of dengue disease. This study was to identify risk factors to management based on a problem solving framework through a family medicine approach. Primary data by history taking, physical examination and home visits. Secondary data from patient medical records. Assessment based on a holistic diagnosis in a qualitative and quantitative. The results is functional grade 2 patients with DHF, internal risk factors namely lack of knowledge about the disease and prevention. External risk factors are piles of goods next to the patient's house and piles of clothes in the house that are not arranged, wells and bathtubs in the house that are not closed. Intervention by counseling regarding dengue disease with hygiene and healthy live habits. Evaluation, there has been a slight change in behavior where patients, families and local residents do Burying, Draining, and Closing. Conclusion is that clinical problems in patients require attention in changing hygiene and healthy living behavior which takes time to get a change. Health workers are tasked with solving clinical problems ,finding, and providing solutions to problems in the environment that affect the health of all.